Shaping Christianity in greater China : Indigenous Christians in focus - Woods, Paul, 1966- (Regnum studies in mission., 2017)
This book is an integrated collection of essays looking at the shaping of Christianity in China with a special emphasis on the contributions of Chinese believers. As well as its geographical scope of the China Mainland, Taiwan, and Hong Kong, the material covers a span of time from the end of the Ming Dynasty until the Sichuan earthquake of 2008. Also, Anglicans, Presbyterians, Roman Catholics, Charismatics, and various kinds of independents rub shoulders within its pages. This is, of course, how it should be.